Integrating biodiversity conservation and ecosystem services into operational plan of community forest in Nepal : status and gaps - Thani, P. R.; KC, R.; Sharma, B. K.; Kandel, P.; Nepal, K. (Banko Janakari, 2019)
After initiation of community forestry system in Nepal, the status of forest cover has improved due to significant roles of people in conservation, management and utilization of forest resources. As a result of increased productivity of the forest and restoration of degraded areas, forest users have been able to receive various economic, social, cultural and environmental benefits to strengthen their livelihood. Despite many positive outcomes of community forestry, there are still some factors which haven’t allowed the proper biodiversity conservation and ecosystem services maintenance. The study carried out on 100 operational plans from different parts of the country and it showed that the incorporation status of biodiversity and ecosystem services into community forest operational plan is worse despite the fact that such plan is the main component to lead the destination of any community forest. In addition to this, some gaps and challenges were observed in community forestry which have not favoured to biodiversity conservation and ecosystem services management systematically at an optimum level. Among them, duplication problem of biodiversity and ecosystem services related issues in operational plan; timber oriented operational plan; limited provision about wildlife conservation and negative perception of people on wildlife and their conservation owing to human wildlife conflict; dominant socioeconomic factors; impact of introduced species, invasive and alien species; lacking in provision of adaptation and mitigation methods to cope with impact of climate change on biodiversity and ecosystem services and shrinking of biological corridor due to habitat fragmentation were major issues. Besides this, to address these issues, it was also identified from the national consultation workshop of forest officials and experts that most appropriate uniform methods, measures and mechanisms are needed to be developed for the complete assessment, prioritization, analysis and development of action plans to main stream biodiversity conservation and ecosystem services management into operational plan of community forestry.